Strategi Pengembangan Usaha Agroindustri Sagu di Desa Asaki Kecamatan Lambuya Kabupaten Konawe - Siti Yuliani; Sarty Syarbiah; Abu Rahman (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
The purpose of this study was to determine the internal and external factors of sago agro-industry development and to identify the strategy for developing sago agro-industry in Asaki Village, Lambuya District, Konawe Regency. The determination of the location of this study was carried out purposively, which is a method of determining the research area intentionally. The population in this study were all farmers who were in the sago agro-industry in Asaki Village, Lambuya District, Konawe Regency, where the number was 36 people. The sample determination was carried out by census, namely by taking all populations as research samples. The analysis used the SWOT formula. The results of the study Internal factors are strength factors consisting of seven, namely: quality products at affordable prices, strategic production locations, experience in business, having their own sago plantation land, products without preservatives and bleach, accepting orders in advance. Weakness factors consist of five, namely: small production results, no regular consumers, production is carried out with traditional equipment, lack of supporting facilities, only relying on the capital of the business owner. External factors are opportunity factors consisting of six opportunity factors, namely: high consumer purchasing power, high demand for sago products, it is a staple food for the community, raw materials are easy to obtain, the availability of raw materials is guaranteed, more modern production machines have been created. Threat factors consist of five factors, namely: many competitors, no government assistance, increasing fuel prices, unstable raw material prices, changes in weather or climate and sago agroindustry is on the medium line or Hold and maintain strategy, which means that the processing business is maintained, maintained and improved where the Hold and maintain strategy is a profitable situation that has opportunities and strengths, so that it can take advantage of existing opportunities.